(untitled) (Perner’s Contacts, 2009)
The paper deals with an issues of urban public transport system quality, especially with its characteristic, area of quality review, quality quantification, advice qualify review and the elements of quality in particular modules - transport infrastructure, means of transportation, information and control of urban public transport system..